Exploring Socio-Demographic Determinants and Geographical Variations in Epidemiological Patterns of Hepatitis C: A Nationwide Analysis - 7Ali Asghar Mirjat, 8Kashif Lodhi, 9Firas S. Azzeh, 1Amjad Ali, 2Saleemullah, 3Memoona Fareed, 4Dr Hameed Mumtaz Durrani, 5Dr Sheema Khan, 6Dr Anisa Bashir (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Hepatitis C infection is a significant public health concern globally, with variations observed across socio-demographic factors and geographical regions. Understanding these determinants and variations is crucial for effective disease management and prevention strategies. Aim: This study aimed to explore the socio-demographic determinants and geographical variations in the epidemiological patterns of Hepatitis C infection on a nationwide scale. Methods: A comprehensive nationwide analysis was conducted using epidemiological data collected from diverse sources. Socio-demographic variables including age, gender, income levels, and educational attainment were analyzed alongside geographical factors such as urbanization and regional disparities. Statistical methods including regression analysis and geographic mapping were employed to assess the relationships between these variables and the incidence/prevalence rates of Hepatitis C. Results: The analysis revealed notable socio-demographic determinants influencing the epidemiological patterns of Hepatitis C. Factors such as lower income levels, educational disparities, and certain age groups were associated with higher prevalence rates. Additionally, geographical variations highlighted hotspots of infection prevalence, with certain regions exhibiting significantly higher rates compared to others. Conclusion: This nationwide analysis provides valuable insights into the socio-demographic determinants and geographical variations affecting the epidemiological patterns of Hepatitis C. The findings underscore the importance of targeted interventions tailored to specific demographic groups and geographical regions for effective disease control and prevention efforts